Functional performance testing and return to sport criteria in patients after anterior cruciate ligament injury 12–18 months after index surgery: A cross-sectional observational study - Leister, Iris; Kulnik, Stefan Tino; Kindermann, Harald; Ortmaier, Reinhold; Barthofer, Jürgen; Vasvary, Imre; Katzensteiner, Klaus; Mattiassich, Georg (Physical therapy in sport, 2019)
Objective return to sport (RTS) criteria after anterior cruciate ligament (ACL) injury are lacking. Study purposes were (1) to report Limb Symmetry Index (LSI) values achieved in a test battery, (2) to detect how many subjects meet RTS criteria 12–18 months post-operative and (3) to identify whether patient-administered scores predict RTS criteria. Observer-blinded, cross-sectional observational study. Traumacenter Linz, Austria. Eighty-eight subjects (48 females; mean (SD) age: 34.73 (10.8) years); Twenty-five had undergone ACL repair (IB), 21 ACL reconstruction (AI). Forty-two healthy subjects served as control. Participants were evaluated using a single-leg hop test battery. The variable of interest was meeting the RTS criteria by reaching defined cut-off values. Logistic regression was used to investigate the relationship between subjective scores (IKDC, WOMAC, KOOS, Lysholm) and fulfillment of RTS criteria. Additionally, subjective physical activity and anterior knee translation were assessed. Thirty-six percent of IB patients and 28.6% of AI patients met RTS criteria. None of the included scores produced significant odds to predict RTS. Subjective scores, clinical examinations and fulfillment of RTS criteria did not differ significantly between groups. Maximum anterior translation revealed a significant difference (p = 0.009) in favor of the AI group. •A premature return-to-sport attempt might contribute to re-injury of the knee.•Knee scores did not produce significant odds to predict return-to-sport criteria.•Functional testing is recommended before return-to-sport.